REPRESENTASI KEKERASAN SEKSUAL PADA PEREMPUAN (Studi Analisis Semiotika dalam Film â7 Hati 7 Cinta 7 Wanitaâ) - Valerina, Wisti (KOMUNITAS, 2013)
The globalization implies the existence of an infinite information. Furthermore, the audience themselvesÂ  toÂ  beÂ  smartÂ  inÂ  choosingÂ  andÂ  receiveÂ  informationÂ  onÂ  getÂ  it.Â  OneÂ  ofÂ  mediumÂ  isÂ  film. Various types of films that update will become a factor in the audience to absorb the information that is in the vicinity. Information about sexual violence on women, for example, will always be a hot topic discussed due to rampant cases of sexual violence involving women as victims. This study aims to determine the sexual assault case that represented in the film â7 Hati 7 Cinta 7 Wanitaâ. ThisÂ  caseÂ  mayÂ  beÂ  existingÂ  inÂ  ourÂ  neighbourhood.Â  ThisÂ  filmÂ  givesÂ  taughtÂ  toÂ  women,Â  especially Indonesian women not to dissolve into the feelings and in the end only be a mere victim. ThisÂ  researchÂ  isÂ  aÂ  qualitativeÂ  studyÂ  usingÂ  semiotic analysis.Â Â  ResearchÂ  showsÂ  thatÂ  filmÂ  â7 HatiÂ  7Â  CintaÂ  7Â  WanitaâÂ  hasÂ  fiveÂ  elementsÂ  ofÂ  sexualÂ  violenceÂ  onÂ  womenÂ  byÂ  theÂ  National CommissionÂ  onÂ  ViolenceÂ  AgainstÂ  WomenÂ  (KomnasÂ  Perempuan)Â  whichÂ  isÂ  probablyÂ  theÂ  result representationÂ  ofÂ  whatÂ  isÂ  aroundÂ  us.Â  FiveÂ  elementsÂ  are:Â  (1Â  )Â  SexualÂ  Harassment,Â  (2)Â  Sexual Torture, (3) Abortion Coercion, (4) Forced Marriage,Â  and (5) TraffickingÂ  ofÂ  Women forÂ  Sexual Purposes. The five elements, perhaps even to the 15elements of sexual violence on women already in the grade by the National Commission for Women are there around us.